2018
DOI: 10.4103/aer.aer_206_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between propofol and dexmedetomidine for conscious sedation in patients undergoing outpatient colonoscopy

Abstract: Introduction:Colonoscopy is a mildly painful procedure requiring conscious sedation. Though propofol is a widely used anesthetic agent in day-care procedures due to its rapid onset and quick recovery has a drawback of requiring resuscitation maneuvers more often than the conventional methods. Dexmedetomidine, a newly introduced, highly selective α2-adrenergic receptor agonist possessing hypnotic, sedative, anxiolytic, sympatholytic, and analgesic properties with impressive safety margin, needs to be explored f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…For our dosing of both dexmedetomidine and fentanyl-propofol, we did not find any significant variations in heart rate or mean blood pressure, which may be related to our use of glycopyrrolate prophylactically to prevent bradycardia and extrasystoles in some patients. Our findings coincide with the results of Karanth et al 10 . They evaluated an initial dose of propofol 2-3 mg kg -1 over 10 min followed by a continuous infusion of 25 µg kg -1 min -1 in one group and compared it to another group where they started a bolus dose of dexmetatomidine 1 µg kg -1 intravenously over 10 min followed by a maintenance infusion of 0.2 µg kg -1 h -1 until the end of the procedure.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…For our dosing of both dexmedetomidine and fentanyl-propofol, we did not find any significant variations in heart rate or mean blood pressure, which may be related to our use of glycopyrrolate prophylactically to prevent bradycardia and extrasystoles in some patients. Our findings coincide with the results of Karanth et al 10 . They evaluated an initial dose of propofol 2-3 mg kg -1 over 10 min followed by a continuous infusion of 25 µg kg -1 min -1 in one group and compared it to another group where they started a bolus dose of dexmetatomidine 1 µg kg -1 intravenously over 10 min followed by a maintenance infusion of 0.2 µg kg -1 h -1 until the end of the procedure.…”
Section: Discussionsupporting
confidence: 94%
“… 9 An optimal sedative medication should have extensive therapeutic evidence and anticipated pharmacodynamics to ensure adequate sedation. 10 Dexmedetomidine exhibits a synchronized sedation pattern, enabling patients to transition quickly from a state of sleepiness to wakefulness, follow instructions while conscious, and return to sleep when not stimulated. 11 The use of propofol for colonoscopy procedures was more satisfactory than dexmedetomidine infusions to patients in the Kavousi et al 2 study, but on the other hand, there were recordings of respiratory depression in many patients who needed respiratory and airway support.…”
Section: Discussionmentioning
confidence: 99%
“…The ndings of the present study, comparing the results of the PF and DK groups, showed that patients who received PF had signi cantly higher sedation based on their Ramsey score. A study by Karanth et al, (8) comparing the e cacy and side effects of Dexmedetomidine and Propofol in sedation of patients undergoing colonoscopy shows that there was no signi cant difference in analgesic effects between the two agents. This nding was different from that of the current study, although in the present study, despite the higher sedation score in the PF group, there was no signi cant difference between the two groups in the satisfaction degree of the physician and patient with the procedure and pain reported by patients in recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of sedation is conscious sedation. Several medications as opioids, ketamine, and midazolam have been used alone or with propofol as a combination and have been linked to adverse effects as respiratory depression (2) . Dexmedetomidine is considered a potent highly selective α2-adrenergic receptors (AR) agonist as these receptors have been found in the central & peripheral nervous system (spinal cord), also found in the platelets and many organs such as the liver, pancreas, kidneys, and eyes.…”
Section: Introductionmentioning
confidence: 99%